STANDARDISASI EKSTRAK PEGAGAN, CENTELLA ASIATICA SEBAGAI OBAT HERBAL TERSTANDAR HEPATOPROTEKTOR - Puspa Dewi N Lotulung; Sri Handayani; Teni Ernawati; Tri Yuliani; Nina Artanti; Tjandrawati Mozef (Jurnal Kimia Terapan Indonesia, 2015)
Herbal medicinal products would be affected by the quality of raw materials. In turn, the quality of raw material will also be influenced by various factors such as soil conditions, cultivation, post-harvest processing, and the processing of raw materials into crude drug or extract. Therefore, in order to make good herbal medicines, it is necessary to make standardization of herbal extracts that produced herbal medicines that have the same quality and functions of effectiveness in each process. From preliminary studies that have been done, Centella asiatica is one of the potential plants as a source of hepatoprotective compounds. Test in vivo and in vitro against Centella asiatica extracts have shown very good results. Ethyl acetate extract with 17.5 mg/kg of doses body weight and butanol 228.8 mg/kgof doses body weight has been applied for in vivo test using mice induced by CCl4; theydemonstrated hepatoprotective effects. Ethyl acetate extracts were able to reduce levels of the enzyme alanine aminotransferase (ALT) and aspartate aminotransferase (AST) by 56 % and 44 % respectively while butanol extract can reduce the enzymes AST levels by 3%. Standardizationof Centella asiatica extract performed in this study was the characterization of the extract in the form of non-specific and specific parameters corresponding to the reference of PPOMN (Ministry of health Republic of Indonesia, 2000) such as levels of drying shrinkage, ash content, total plate count microbial contamination, levels of water-soluble compounds, levels of compounds that are soluble in ethanol, phytochemical test, total phenolic content, total flavonoid content and the determination of Pb and Cd weight.The results showed that non-specific parameters for the ethanol extract of Centella asiatica were requirements based on Herbal Pharmacopoeia in 2008 which includes parameters such as determination of shrinkage on drying â‰¤ 10%, ash content â‰¤ 16.6% and negative microbial contamination. Specific parameters for the ethanol extract of Centella asiatica have met the requirements of Herbal pharmacopeia in 2008.Keywords: Centellaasiatica, hepatoprotective, standardized herbal medicine, specificparameters, and non-specific parameters